Tumour recurrence is associated with Jass grouping but not with differences in E-cadherin expression in moderately differentiated Dukes' B colorectal cancers. - Ilyas, M; Novelli, M; Wilkinson, K; Tomlinson, I; Abbasi, A; Forbes, A; Talbot, I (1997)
AIMS: To assess whether immunohistochemical expression of the putative invasion suppressor, E-cadherin, is associated with tumour recurrence in colorectal cancer, independent of Dukes' stage and degree of differentiation, and thus to determine whether measurement of E-cadherin is clinically useful. METHODS: 90 moderately differentiated Dukes' B colorectal carcinomas from patients who had been followed up for at least six years were examined. All were from curative resections performed at St Mark's Hospital and the tumours were shown, on histology, to be clear of all resection margins. Tumours were reviewed and additionally classified in accordance with the Jass grouping system. Immunohistochemical analysis of E-cadherin expression was performed for each tumour using the monoclonal antibody HECD 1. RESULTS: The Jass group ranged between I and III and there was a significant association between Jass group and tumour recurrence (p < 0.05). Positive E-cadherin expression was seen in 40/69 (58%) of non-recurrent and 13/21 (62%) recurrent cases respectively. There was no significant difference in E-cadherin expression between the two groups of tumours. CONCLUSIONS: Even when controlled for Dukes' stage and differentiation, the Jass grouping system yields useful prognostic information; E-cadherin, however, does not predict outcome in the important group of moderately differentiated Dukes' B colon cancers, and may be of little independent prognostic value in other colon cancers.